Guidelines for Promoting the Competency of Civil Servants and Employees of the Pa Kha Luang Subdistrict Administrative Organization Ban Luang District, Nan Province - Salaenoy, Karnsith; Phureephong, Krit; Suwansri, Pramual; Suwansak, Termsak; โพธิ์ทัศน์ อัญชลี (Journal of Dhamma for Life, 2025)
The research aims to study the factors related to the positions of government officials and employees that affect key competencies, including goal orientation, service excellence, professional expertise, ethics, and collaborative knowledge. Data were collected from a total of 71 personnel in the organization, comprising 19 government officials, 9 permanent employees, and 43 temporary employees. The research utilized questionnaires as a tool for data collection and analysis, employing frequency, percentage, mean, standard deviation, t-tests, and One-Way ANOVA for hypothesis testing. The findings indicate that, overall, employees exhibit a high level of competency for their positions. When comparing personal data with competencies, significant differences were found among employees in different positions concerning goal orientation and ethics, with statistical significance at the .05 level. However, no significant differences were observed in other aspects. Therefore, to enhance competency in employee performance, it is recommended to establish a shared vision, policies, and objectives at both the organizational and sub-unit levels, providing a unified direction for government officials and employees. The ultimate goal is the success of the organization.